Temporal and spatial patterns and determinants of traditional villages in Henan Province - Man Zhang; Jiabin Wu; Yu Liu (PLoS ONE, 2026)
Traditional villages are important carriers of China’s cultural heritage and reflect long-term interactions among history, environment, and human settlement. This study examines 1,035 officially recognized traditional villages in Henan Province to identify their spatiotemporal distribution patterns and associated factors. Using ArcGIS-based spatial analysis, GeoDetector, the spatial lag model, and historical literature review, we find that traditional villages show significant spatial clustering and clear regional inequality. High-density clusters occur in northern Henan (Anyang–Hebi), central Henan (Pingdingshan), and southern Henan (Xinyang), whereas eastern Henan remains sparsely distributed, partly due to the long-term impacts of Yellow River flooding. The evolution of village distribution can be divided into four major historical stages, and the dominant spatial orientation shifted from a southwest–northeast trend before the Ming period to a southwest–northeast trend thereafter. Descriptively, village concentration is associated with moderate elevation, proximity to water, lower GDP levels, and intermediate distance from county-level central cities. However, after spatial autocorrelation was controlled for, these variables were not statistically significant as independent predictors in the spatial lag model, suggesting that village distribution is shaped more by combined effects and spatial spillover than by single factors alone. These findings provide evidence for cluster-based heritage protection in Henan and offer broader lessons for historically layered inland regions facing rural transformation and urbanization pressures.